Development and Validation of Digital Literacy Scale (DLS) and its Implication for Higher Education - Hina Amin; Muhammad Abid Malik; Bulent Akkaya (International Journal of Distance Education and E-Learning, 2022)
The study aimes to develop and validate Digital Literacy Scale (DLS) based on Chen’s (2015) theoretical framework which includes nine dimensions: communication, collaboration, critical thinking, creativity, citizenship, character, curation, copyright, and connectedness. A question pool consisting of 62 items based on the nine dimensions of digital literacy was generated on a 5-point Likert-type scale. Content validity of the question pool was sought from experts in terms of clarity of items, language understanding, and relevance. SPSS and AMOS were used for statistical analysis. Using a sample of 349 university students, Exploratory Factor Analysis was employed for reliability analysis, construct validation, and factor structure of the scale. EFA confirms the nine dimensions; however, some items were deleted during this process. Finally, Confirmatory Factor Analysis was employed to check the reliability and validity of the factor structure by using a second sample (n=442). CFA showed that all the values were within the acceptable range (Kaiser-Meyer-Olkin 0.886, the total variance explained 62.87%, Cronbach Alpha 0.894, and the goodness of fit 0.924). Thus a standardized DLS consisting of 36 items and 9 factors (communication, copyright, critical thinking, character, citizenship, curation, connectedness, creativity, and collaboration) was finalized. DLS is a psychometrically sound, reliable, and valid measurement tool that can be used to measure digital literacy.